Impact of combined hydrogen plasma and transient heat loads on the performance of tungsten as plasma facing material. (10th November 2015) - Wirtz, M.; Bardin, S.; Huber, A.; Kreter, A.; Linke, J.; Morgan, T.W.; Pintsuk, G.; Reinhart, M.; Sergienko, G.; Steudel, I.; De Temmerman, G.; Unterberg, B.
Abstract: Experiments were performed in three different facilities in order to investigate the impact of combined steady state deuterium plasma exposure and ELM-like thermal shock events on the performance of ultra high purity tungsten. The electron beam facility JUDITH 1 was used to simulate pure thermal loads. In addition the linear plasma devices PSI-2 and Pilot-PSI have been used for successive as well as simultaneous exposure where the transient heat loads were applied by a high energy laser and the pulsed plasma operation, respectively. The results show that the damage behaviour strongly depends on the loading conditions and the sequence of the particle and heat flux exposure. This is due to hydrogen embrittlement and/or a higher defect concentration in the tungsten near surface region due to supersaturation of hydrogen. The different results in terms of damage formation from both linear plasma devices indicate that also the plasma parameters such as particle energy, flux and fluence, plasma impurities and the pulse shape have a strong influence on the damage performance. In addition, the different loading methods such as the scanning with the electron beam in contrast to the homogeneous exposure by the laser leads to an faster increase of the surface roughness due to plastic deformation.